PILOT CASE-STUDY ON E-TRAINING BY PERSONS OF INDIAN ORIGIN (PIO) FOR WOMEN DIGITAL ENTERPRISES, IN SOUTH INDIA - Guruprasad (Digital Repository of Theses, 2023)
This small-scale pilot case-study research has the objectives to make original contributions to the virtual or online, custom-made, on-the-job, e-training programs for women entrepreneurs & their female employees in selected locations of southern India and verifying the feasibility of work-from-home or remote working e-business models, by building minimum viable products (MVPs) which could be eventually scaled to bigger businesses. Initially, the e-training has been guided by persons of Indian origin (PIO) with in-depth exposure, skills, & knowledge in the business coaching & start-up/SME ecosystem on global levels and who are building the capacities in international business leadership. The researcher has collected primary & secondary data for about four and a half months (about 18 weeks), from early November 2022 until mid-March 2023, to conduct this research. Using qualitative methodologies & research instruments such as semi-structured or unstructured questionnaires, a total mix of 275 interviews & personal observations have been done with the help of about 100 women digital entrepreneurs/management staff, 100 female e-staff, 25 persons of Indian origin (PIO), 25 digital training providers, and 25 overseas customers from Australia. The female stakeholders of women enterprises with a good school or college education & computer/digital literacy, between the age group of 20 to 45 years, have been selected from the six cities/towns, i.e., Hyderabad, Machlipatnam, Mysuru, Kodagu, Ooty, & Wayanad to collect the research data to represent the five southern states of India, i.e., Telangana, Andhra Pradesh, Karnataka, Tamil Nadu, & Kerala, to conduct this small scale pilot case-study. The results of this small-scale pilot case-study research provide an initial understanding and feedback on the hypotheses that utilising the e-training programs to achieve pre-defined e-business goals & objectives on a smaller scale is feasible. The findings of this small-scale pilot case study can be used in related industry segments to assist in definitive, full-scale research and pave a path to the stakeholders for lifelong learning (LLL) in international business leadership and to add value to the local & global communities in a subtle, grateful and humble manner.